Isolation of bis(η2-nitrato)(η4-cyclobutadiene)cobalt(II) complexes from the oxidation of sterically hindered CpCo-stabilized cyclobutadiene complexes - Schaefer, Carsten; Gleiter, Rolf; Rominger, Frank (Organometallics, 2004)
The oxidation of sterically hindered, CpCo-protected cyclobutadienes with ceric ammonium nitrate (CAN) yielded the paramagnetic Co(NO3)2-protected cyclobutadiene products. These half-sandwich complexes represent possible intermediates within the mechanism of the CAN decomplexation of CpCo−cyclobutadiene complexes.
Im Titel erscheinen die Ziffern 2 und 4 hochgestellt
Gesehen am 11.11.2020